TINJAUAN PENGELOLAAN JARINGAN IRIGASI BENDUNG MENCONGAH KABUPATEN LOMBOK BARAT - ALFREDO VINCENSIUS DOWA BILLY; MUHAMAD YAMIN; AMINULLAH AMINULLAH (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The purpose of this study was to determine the water balance, and water supply system in the group of farmes using the P3A Mencongah weir. The method used in calculating the maximum rainfall is the Gumbel method. After analyzing the availability of water for irrigation on the Mencongah Weir irrigation network during the growing season it is fulfilled, where the minimum discharge is 9,445 m3/sec, while the water demand at the farmer level is 6.139 m3/sec.The provision of water at the farmer level during the growing season for the four WUA groups (Water User Farmers Assocoation) at Mencongah Weir continuously, and in rotation